2009
DOI: 10.1002/lapl.200810112
|View full text |Cite
|
Sign up to set email alerts
|

532 nm continuous wave mode-locked Nd:GdVO4laser with SESAM

et al.

Abstract: Abstract:We obtain continuous wave mode-locked Nd:GdVO 4 -KTP laser with a SESAM. This is the first report of CW modelocked Nd:GdVO 4 -KTP laser with a SESAM to our knowledge. 396 mw CW mode-locked pulse is achieved at the incident power of 7.653 W, with the repetition about 95 MHz. The pulse duration is assumed to be 5.5 ps, this is the shortest green pulse of 532 nm with SESAM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(25 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“…In our opinion, three factors limit the efficiency: astigmatism loss induced by the concave foldmirror [7,8,[11][12][13], relatively low transmittance at 532 nm and reflection at 1064 nm of the dichroic fold-mirror, difficulties in adjusting the complex system. In order to avoid the above factors limiting the efficiency, we adopted a straight cavity introduced in [14,15].…”
Section: Introductionmentioning
confidence: 98%
“…In our opinion, three factors limit the efficiency: astigmatism loss induced by the concave foldmirror [7,8,[11][12][13], relatively low transmittance at 532 nm and reflection at 1064 nm of the dichroic fold-mirror, difficulties in adjusting the complex system. In order to avoid the above factors limiting the efficiency, we adopted a straight cavity introduced in [14,15].…”
Section: Introductionmentioning
confidence: 98%
“…Another vanadate crystal, Nd:GdVO 4 , which was confirmed to be supe rior to Nd:YVO 4 in thermal properties, was also inves tigated extensively. The research to output wavelengths involving Nd:GdVO 4 crystals were mostly focused at 1063 nm [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30], 1341 nm [31][32][33][34][35][36][37], and 912 nm [38][39][40][41][42][43]. However, through the analysis of a spectroscopic study has demonstrated that there are three or four emission bands on the F 3/2 -I 11/2 transition of Nd:GdVO 4 crystal.…”
Section: Introductionmentioning
confidence: 99%
“…Since semiconductor saturable absorber mirrors (SESAMs) were successfully developed two decades ago [1], they have been widely used for ultrashort pulse generation in passively mode locked solid state lasers [2][3][4][5][6][7]. However, SESAMs have encountered two major practical concerns such as the short operation wavelength range and the high cost.…”
Section: Introductionmentioning
confidence: 99%